A Secured and Efficient Anonymous Roaming Scheme of Mobile Internet. (9th March 2022) - Cheng, Yao; Yue, Li; Duan, Naixia; Li, Chenglong
Abstract : An anonymous roaming scheme of mobile Internet was discussed in this paper aiming to improve the traditional authentication protocol that cannot satisfy the demand of user's identity authentication when the mobile terminal is roaming in mobile Internet. The authentication server of remote network will complete the identity legitimacy verification of mobile terminal with the help of the home network authentication server. A temporary identity is used to prevent user's anonymity protection from being tracked and eavesdropped, as well as other attacks, which can improve the confidential of user's identity and location considerably. This anonymous roaming scheme can achieve a high-level of safety efficiently. This will also satisfy the development of the network technology.